Rappaport as speaker and demiurge - Belov, Mikhail (project baikal, 2025)
The article features the talent of A. G. Rappaport as a well-educated speaker. The author refers to the history of his family. He also emphasizes Rappaport’s nontrivial approach to architectural theory.
Keywords: style; aristocracy; “Paper architecture”; speaker